The implicit midpoint rule for nonexpansive mappings in 2-uniformly convex hyperbolic spaces. Issue 1 (22nd February 2019) - Fukhar-ud-din, H.; Khan, A.R.
Abstract : The purpose of this paper is to introduce the implicit midpoint rule (IMR) of nonexpansive mappings in 2- uniformly convex hyperbolic spaces and study its convergence. Strong and △ -convergence theorems based on this algorithm are proved in this new setting. The results obtained hold concurrently in uniformly convex Banach spaces, CAT( 0 ) spaces and Hilbert spaces as special cases.